2013
DOI: 10.4149/bll_2013_095
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum adiponectin and prognosis in patients with heart failure

Abstract: Abstract:Background: The role of adiponectin in the development of cardiac disease remains less clear than in metabolic disorders. While some studies indicated that low adiponectin levels were associated with cardiovascular disease, not all studies have been able to show such association. Adiponectin levels may infl uence the development of chronic heart failure, but the epidemiological data are somewhat complex. Thus, the aim of this study was a survey of relationship between serum Adiponectin and prognosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…The 1-year mortality rate significantly elevated to 2.6-fold when the plasma NP-pro BNP above 2060 ng/L [28], or increased to 7.0-fold with the plasma NP-pro BNP above 10,000 ng/L [16]. Another outpatient-based investigation by Sokhanvar et al [14], which enrolled patients with systolic HF, also disclosed that the level of plasma NT-proBNP was positively correlated with mortality and morbidity at a follow-up period of six months. Besides, the study by Gardner et al [15] found that, for advanced chronic HF patients, a single level of plasma NT-proBNP >1505 ng/L (the median level of the participants) independently predicted of all-cause mortality within 554 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1-year mortality rate significantly elevated to 2.6-fold when the plasma NP-pro BNP above 2060 ng/L [28], or increased to 7.0-fold with the plasma NP-pro BNP above 10,000 ng/L [16]. Another outpatient-based investigation by Sokhanvar et al [14], which enrolled patients with systolic HF, also disclosed that the level of plasma NT-proBNP was positively correlated with mortality and morbidity at a follow-up period of six months. Besides, the study by Gardner et al [15] found that, for advanced chronic HF patients, a single level of plasma NT-proBNP >1505 ng/L (the median level of the participants) independently predicted of all-cause mortality within 554 days.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the longer plasma half-life and lower intra-individual biological variation, NT-proBNP is considered a more reliable biomarker than BNP in clinical practice. Clinically, the plasma NT-proBNP level grossly reflects cardiac structure and function in HF patients [10,11,12], has good diagnostic performance for discriminating acute HF from a noncardiac entity in patients with new-onset dyspnea, and has good prognostic–predictive power in HF patients [13,14,15,16,17]. Noveanu et al [17] conducted a study to compare the prognostic–predictive power of individual NT-proBNP level obtained at different time points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin, an adipocyte-specific cytokine, exhibits anti-inflammatory property and protective effects against obesity-related diseases (6). Circulating adiponectin level was increased in patients with heart failure irrespective of etiologies (7 9), implying substantial potential as a prognostic biomarker. However, adiponectin appears to lose its cardio-protective and anti-inflammatory properties in heart failure patients (10).…”
Section: Introductionmentioning
confidence: 99%
“…Even more, a positive association between inflammation and APN is usually reported in chronic HF [23]. Higher levels of circulating APN are also linked to the poor outcome of patients with chronic HF [24][25][26][27]. It is still questionable if APN loses its anti-inflammatory and cardioprotective activity in chronic HF, or the compensatory increase of APN in serum is unable to counteract the increasing pro-inflammatory milieu [5].…”
Section: Introductionmentioning
confidence: 99%